Trends in undergraduate economics degrees, 2001–2018. Issue 3 (3rd July 2019) - Siegfried, John J.
Abstract: Undergraduate degrees awarded in economics by U.S. colleges and universities were stagnant from 2010 (2009–10) through 2013, increased rapidly (almost 15%) over the two years from 2013 through 2015, but have subsequently leveled off in 2016 through 2018.